ANALISIS DAMPAK KEGIATAN PERTAMBANGAN BATUBARA TERHADAP LINGKUNGAN DAN EKONOMI MASYARAKAT DI KABUPATEN KOTABARU - Elsa Asriana; Rosalina Kumalawati; Ellyn Normelani (Pelantar Press, 2023)
Coal mining in Kotabaru Regency plays a significant role in the regional economy by increasing local revenue, absorbing labor, and fostering the growth of community-supporting businesses. However, this activity also has serious environmental impacts, such as water pollution, air pollution, and the reduction of productive land. This research uses a descriptive qualitative approach, utilizing literature, agency reports, and field observations. The analysis reveals an imbalance between short-term economic benefits and long-term ecological losses. Therefore, a sustainable mine management strategy is needed through reclamation, waste management, and environmental policies that actively involve the community.